تأثير النظام الضريبي على السياسة النقدية في العراق للمدة (2010-2022) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Taxes are defined as mandatory contributions imposed on individuals or companies by a government entity, whether local, regional, or national. Taxes can be imposed in more than one form, they can be direct or indirect on taxpayers, and taxes can have a positive impact on monetary policy. It is noted that the tax system in Iraq needs reforms because the tax revenues collected during the study period were low, so they had no effect on stimulating economic activity. The research concluded that it is necessary to reform the tax system to have an effective financial resource, especially since the tax capacity in Iraq was not exploited. The correct format.